2022
DOI: 10.3390/antibiotics11060733
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication with Antibiotics during COVID-19 in the Eastern Mediterranean Region Countries: A Review

Abstract: Self-treatment with medicines including treatment with antibiotics is a growing global concern, as it can cause public health problems, such as antibiotic resistance and drug toxicity. Therefore, the significance of the self-medication impact of COVID-19 in any region can have an influence on the prevalence of such problems. The review aimed to investigate the self-treatment with antibiotics among the general population in Eastern Mediterranean region countries during COVID-19 pandemic. A comprehensive review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
18
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 40 publications
6
18
0
4
Order By: Relevance
“…In Zambia, findings by Mudenda et al (2022 , 2023) further corroborate these findings, suggesting both a regional and a global increase in reliance on azithromycin. Additionally, research conducted in several Eastern Mediterranean countries, including studies by Kalungia et al (2022) and Jirjees et al (2022) , and in other regions such as Ghana, as noted by Amponsah et al (2022) , has also observed this trend, highlighting a consistent global shift towards increased usage of this particular antibiotic. These studies collectively emphasise the growing preference for azithromycin across diverse geographical and clinical settings ( Mugada et al, 2021 ; Sharma et al, 2021 ; Amponsah et al, 2022 ; Jirjees et al, 2022 ; Kalungia et al, 2022 ; Mohamad et al, 2022 ; Mudenda et al, 2022 ; Mudenda et al, 2023 ).…”
Section: Discussionmentioning
confidence: 65%
“…In Zambia, findings by Mudenda et al (2022 , 2023) further corroborate these findings, suggesting both a regional and a global increase in reliance on azithromycin. Additionally, research conducted in several Eastern Mediterranean countries, including studies by Kalungia et al (2022) and Jirjees et al (2022) , and in other regions such as Ghana, as noted by Amponsah et al (2022) , has also observed this trend, highlighting a consistent global shift towards increased usage of this particular antibiotic. These studies collectively emphasise the growing preference for azithromycin across diverse geographical and clinical settings ( Mugada et al, 2021 ; Sharma et al, 2021 ; Amponsah et al, 2022 ; Jirjees et al, 2022 ; Kalungia et al, 2022 ; Mohamad et al, 2022 ; Mudenda et al, 2022 ; Mudenda et al, 2023 ).…”
Section: Discussionmentioning
confidence: 65%
“…There was also misinformation in various media outlets about the benefits of some medications for either preventing or treating COVID-19 [ 23 ]. This resulted in an increase in risky self-medication with several over-the-counter medications [ 2 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the efficient removal of antibiotics during wastewater treatment is crucial for public health, in addition to removal of heavy metals, especially in light of current postpandemic scenarios. 4 According to the Codex Alimentarius regulation and European Union (EU), a maximum residue limit for amoxicillin (AMX) is 10 ng mL −1 . 5 Until now, the AMX detection is mainly based on instrumental methods such as liquid chromatography coupled to tandem mass spectrometry (LC−MS), 6 capillary electrophoresis, 7 high performance liquid chromatography, 8 spectrofluorometry, 9,10 electrochemical sensors, 11 fluorescence sensors, 12 ion mobility spectroscopy, 13 and enzymatic quantification.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, the removal of health-threatening pollutants from wastewater before its discharge into the environment is of the utmost importance. Therefore, the efficient removal of antibiotics during wastewater treatment is crucial for public health, in addition to removal of heavy metals, especially in light of current postpandemic scenarios . According to the Codex Alimentarius regulation and European Union (EU), a maximum residue limit for amoxicillin (AMX) is 10 ng mL –1 .…”
Section: Introductionmentioning
confidence: 99%